IMPLEMENTASI PEMBELAJARAN TEMATIK MODEL SEQUENCED DI SEKOLAH DASAR - Halida Rohimatul Aini; Ida Ermiana; Galang Ijtihad; Helma Urfiani; Hesti Karisa (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
The learning process prioritizes student activity and provides direct experience. To achieve this, a learning model is used, this study aims to gain a deeper understanding of the implementation of the sequenced learning model during the teaching and learning process in class IV (four) at SDN 25 Cakranegara. The research method used is observation and interviews with teachers. The results of the study showed differences in student activity when given individual assignments. When the sequenced model is applied, students tend to be more active in asking the teacher about the worksheets given. This indicates that the sequenced model can trigger higher student involvement in the learning process.